Transplantation for colorectal metastases: on the edge of a revolution - Andres, Axel; Oldani, Graziano; Berney, Thierry; Compagnon, Philippe; Line, Pål-Dag; Toso, Christian (Translational Gastroenterology and Hepatology; Vol 3 (September 2018): Translational Gastroenterology and Hepatology, 2018)
Liver transplantation (LT) has become the standard of care for selected primary and secondary malignancies. Considered a contra-indication to transplantation until recently, unresectable colorectal liver metastases (CRLM) have gained interest since the publication of the SECA trial by the University of Oslo. It showed a 5-year overall survival of 60%, comparable to the one of standard transplant indication. This report generated multiple questions about the place of LT for CRLM and gave raise to several trials aiming at answering them. The present review is exploring this topic, defining the current state of the field, and extrapolating the future milestones.